Urban Vibrancy and Corporate Growth - DOUGAL, CASEY; PARSONS, CHRISTOPHER A.; TITMAN, SHERIDAN (Journal of Finance, 2015)
ABSTRACT We find that a firm's investment is highly sensitive to the investments of other firms headquartered nearby, even those in very different industries. A firm's investment also responds to fluctuations in the cash flows and stock prices ( q ) of local firms outside its sector. These patterns do not appear to reflect exogenous area shocks such as local shocks to labor or real estate values, but rather suggest that local agglomeration economies are important determinants of firm investment and growth.